Historical theology : an introduction to Christian doctrine : a companion to Wayne Grudem's Systematic theology - Allison, Gregg R.; Grudem, Wayne A. (Grand Rapids, Mich. : Zondervan, 2011)
Most historical theology texts follow Christian beliefs chronologically, discussing notable doctrinal developments for all areas of theology according to their historical appearance. And while this may be good history, it can make for confusing theology, with the classic theological loci scattered throughout various time periods, movements, and controversies. In Historical Theology, Gregg Allison offers students the opportunity to study the historical development of theology according to a topical-chronological arrangement, setting out the history of Christian doctrine one theological element at a time. Such an approach allows readers to concentrate on one tenet of Christianity and its formulation in the early church, through the Middle Ages, Reformation, and post-Reformation era, and into the modern period. The text includes a generous mix of primary source material as well, citing the words of Cyprian, Augustine, Aquinas, Luther, Calvin, Barth, and others. Historical Theology is a superb resource for those familiar with Wayne Grudem's Systematic Theology or interested in understanding the development of Christian theology.
Part 1 : the doctrine of the Word of God -- The canon of scripture -- The inspiration of scripture -- The authority of scripture -- The inerrancy of scripture -- The clarity of scripture -- The sufficiency and necessity of scripture -- The interpretation of scripture -- Part 2 : the doctrine of God -- The existence and knowability of God -- The character of God -- God in three persons : the Trinity -- Creation -- Providence -- Angels, Satan, and demons -- Part 3 : the doctrine of humanity -- The creation and nature of humanity -- Sin -- Part 4 : the doctrines of Christ and the Holy Spirit -- The person of Jesus Christ -- The atonement -- Resurrection and ascension -- The Holy Spirit -- Part 5 : the doctrine of the application of redemption -- Election and reprobation -- Regeneration, conversion, and effective calling -- Justification (right legal standing before God) -- Sanctification (growth in likeness to Christ) -- The perseverance of the saints (remaining a Christian) -- Part 6 : the doctrine of the church -- The church : its nature, its marks, and its purposes -- Church government -- Baptism -- The Lord's Supper -- Worship -- Part 7 : the doctrine of the future -- Christ's return and the millennium -- The final judgment and eternal punishment -- The new heavens and new earth.
Includes bibliographical references and indexes.
Keywords: Theology, Doctrinal -- History